Modeling of airflow and particle trajectories in the vicinity of the narrow head-disk interface gap - John, Benzi (2009)
Rarefied gas flow situations are encountered in a wide range of applications that range from hypersonic flow applications in the upper atmosphere to simulation of low speed gas flows in MEMS devices. With the advent of miniaturization, flow in MEMS devices has received considerable attention recently. In a modern hard disk drive (HDD), the head-disk interface (HDI) gap size is of the order of nanometers. Flow at micro- and nano- scales have been found to deviate from the continuum regime and hence the flow in HDI region needs to be modeled by appropriate computational models. Thus the main aim of the work in this thesis has been directed towards the development of appropriate computational models which can predict rarefied and non-equilibrium flow accurately in micro flow applications such as that in the HDI gap. This work focuses on the modeling of air flow characteristics in the vicinity of the HDI gap. Direct Simulation Monte Carlo (DSMC) method has been chosen as the computational model for predicting flow characteristics in the HDI gap in this work. The flow outside the slider falls in the continuum regime and hence demands the use of a hybrid continuum-atomistic method to couple the DSMC model in the HDI region to the Navier-Stokes equations model in regions outside the slider. In this work various flow modeling aspects for micro flow simulations in the HDI gap have been discussed in detail both for a stand-alone DSMC computation and for the case of a hybrid continuum-atomistic simulation when Navier-Stokes equation needs to be coupled to a DSMC solver. The DSMC method has been initially applied to micro flows such as Couette and Poiseuille flows to validate the prediction of various flow features associated with flows at a micro- and nano- scale. As DSMC is a computationally intensive method parallel DSMC codes using Message Passing Interface (MPI) have been developed to compute the flow in the HDI region. Parallel performance metrics and load balancing issues of the parallel DSMC method on various computing platforms illustrating the portability and scalability of the method have been addressed in this work. An appropriate implicit boundary treatment method has been used for implementing the pressure boundary conditions at the inflow and outflow boundaries and has been extended for the case of a three-dimensional DSMC micro flow simulation. Various Reynolds equation gas lubrication models have also been formulated and solved using the finite difference method to compute the pressure distribution in the slider bearing region. A coupled Reynolds-DSMC model has also been proposed for coupling the Reynolds equation model solutions to the DSMC model for situations in which a detailed atomistic simulation is required in any localized region in the vicinity of the HDI gap.